Dampak Tingkat Pengembalian yang Diharapkan, Leverage Keuangan dan Likuiditas terhadap Efesiensi Anggaran Modal - Adeanto Putra Satyatama; Annisa Nurul Pebriyanti; Dewi Nur Azizah; Anastasia Putri; Maria Yovita R. Pandin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the impact of expected rate of return, financial leverage, and liquidity on capital budget efficiency in companies listed on the Indonesia Stock Exchange in 2023. The research method uses a quantitative approach with multiple linear regression analysis techniques. The sample consists of 60 companies selected through a purposive sampling method. The results of the study indicate that simultaneously, expected rate of return, financial leverage, and liquidity have a significant effect on capital budget efficiency. Partially, financial leverage and liquidity have a significant effect on capital budget efficiency, while the expected rate of return does not have a significant effect. The R Square value of 0.264 indicates that 26.4% of the variation in capital budget efficiency can be explained by the three independent variables. The classical assumption test shows that the regression model is free from multicollinearity problems and the residuals are normally distributed. These findings imply that companies need to pay attention to financing structure and liquidity management in order to improve the efficiency of capital budget use.